Creating a business case for quality improvement research : expert views, workshop summary - Chao, Samantha; Institute of Medicine (U.S.). Forum on the Science of Health Care Quality Improvement and Implementation (Washington, D.C. : National Academies Press, 2008)
The Institute of Medicine (IOM) convened the workshop'Creating a Business Case for Quality Improvement and Quality Improvement Research' on October 15, 2007, in Washington, DC, to develop a better understanding of the economic and business disciplines that encourage sustained efforts to improve the quality of health care.
The business case for quality improvement -- The role of federal funders -- Research as a driving force for change -- Breakout groups -- Communicating a value proposition.
Includes bibliographical references (p. 48).
Also available online.
Keywords: Medical care -- United States -- Quality control -- Research; Quality of Health Care -- economics -- United States; Models, Economics -- United States; Research -- economics -- United States